A Systematic Literature Review of Raz-Kids in Teaching Reading - Widihastutik, Amelia; Hartono, Rudi (Journal of Basic Education Research, 2025)
Purpose of the study: The objective of this study is his study ims to evaluate the effectiveness of Raz-Kids in improving students’ reading skills and investigate the effect of Raz-Kids on students during a reading program. Methodology: The method implemented in this study was Systematic Literature Review (SLR). There were 16 papers on implementing Raz-Kids in teaching reading from Google Scholar, SINTA, Science Direct, and ERIC. The step in writing this scientific work is to find the sources of previous studies, examine them, and make conclusions based on the subject of the study. Main Findings: The result showed that Raz-Kids is an effective internet portal that helps students develop reading skills. It also supports students’ enthusiasm and independent learning in reading. The parents and teachers act as support systems to encourage them to achieve their reading goals. However, there are many challenges with Raz-Kids’ use in reading programs. It highlights the need for this portal to be enhanced. Thus, Raz-Kids is a valuable online resource that helps learners develop their reading skills. Novelty/Originality of this study: This review mainly focused on implementing specific internet portals, namely Raz-kids, in teaching reading in EFL Classes. It aims to develop the knowledge of researchers, educators, policymakers, and technology developers concerning the crucial internet portal Raz-Kids in teaching reading and its effect on students’ outcomes.